REVIEW: THE RELATIONSHIP OF DRUGS INFORMATION SERVICES TO CHRONIC PATIENT LOYALTY - Noviani, Lusy; Suharyani, Ine; Yohana (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Patient loyalty is one of the most important factors in drug therapy to achieve successful disease treatment. We conducted a literature review to examine the relationship between drug information services and chronic patient loyalty in pharmacies. The method used was a systematic examination of related studies and articles, using a qualitative approach. The first screening included 50 articles and excluded 9 articles, the second screening excluded 30 articles, and the final articles used in this review were 11 articles. The results showed that drug information services had a positive effect on patient loyalty through the mediation of patient satisfaction. The factors that influence drug information services include the type of drug information, competence of the pharmacist, interpersonal communication, and service time. The factors that influence patient loyalty include trust, commitment, customer value, and switching costs. Keywords: Drug information service, patient loyalty, patient satisfaction, service quality, pharmaceutical service quality, customer satisfaction.